Serodiversity and ecological distribution of Vibrio parahaemolyticus in the Venetian Lagoon, Northeast Italy - Caburlotto, Greta; Haley, Bradd J.; Lleò, Maria M.; Huq, Anwar; Rita R. Colwell (Environmental Microbiology ReportsEnvironmental Microbiology Reports, 2010)
Vibrio parahaemolyticus is a natural inhabitant of estuarine and marine environments constituting part of the autochthonous microflora. This species is associated with human gastroenteritis caused by ingestion of contaminated water and undercooked seafood. During the past several years, the number of V. parahaemolyticus gastroenteritis cases have increased worldwide, causing over half of all food-poisoning outbreaks of bacterial origin. Vibrio populations in water are known to be influenced by environmental factors. Notably, it has been shown that in different parts of the world the distribution of V. parahaemolyticus in the marine environment is related to the water temperature. In this study, we identified environmental determinants affecting distribution of V. parahaemolyticus in the Venetian Lagoon, in the Italian North Adriatic Sea. Data obtained revealed that sea surface temperature constitutes the key factor influencing occurrence of V. parahaemolyticus, but salinity and chlorophyll concentration are also important. Serotyping of a collection of V. parahaemolyticus environmental isolates revealed high serodiversity, with serotypes O3:KUT and O1:KUT, belonging to the ‘pandemic group’, occurring with higher frequency. From our results, we conclude that there is no correlation between serotype and specific geographic site or season of the year. However, certain serotypes were isolated in the Lagoon during the entire 18 months of the study, strongly suggesting persistence in this environment.